PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PERATAAN LABA - Pandu Nugraha; Vaya Juliana Dillak (JRAK, 2018)
Income smoothing is an action performed by the company’s management in order to reduce fluctuations earnings This is done with the motivation to show good performance to investors, by showing stable corporate profits. Income smoothing is done by adding or reducing the company’s actual profit, to be moved to certain period. This study used a quantitative research method. Purposive sampling method was used, that is 59 samples in the period of 3 years. Therefore, the obtained samples were amounted to be 177 in total. Logistic regression analysis was used. The result showed that profitability, leverage and firm size have influence simultaneously significant to income smoothing. Partially, profitability have a positive effect, while the leverage and firm size do not have an effect to income smoothing.